2014
DOI: 10.1073/pnas.1405725111
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of dueling affective reactions to win–win choices

Abstract: Win-win choices cause anxiety, often more so than decisions lacking the opportunity for a highly desired outcome. These anxious feelings can paradoxically co-occur with positive feelings, raising important implications for individual decision styles and general well-being. Across three studies, people chose between products that varied in personal value. Participants reported feeling most positive and most anxious when choosing between similarly highvalued products. Behavioral and neural results suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(137 citation statements)
references
References 64 publications
12
124
1
Order By: Relevance
“…Here we predict that response latencies will be shorter for the high-value than low-value options, consistent with results found for humans (e.g., Madan, Fujiwara, Gerson, & Caplan, 2012;Shenhav & Buckner, 2014 (Shapiro, Siller, & Kacelnik, 2008). This prediction is also convergent with the notion that a fundamental purpose of movements is to obtain rewards, leading people to move faster when a higher value reward is the predicted goal (e.g., Haith, Reppert, & Shadmehr, 2012;Madan, 2013).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here we predict that response latencies will be shorter for the high-value than low-value options, consistent with results found for humans (e.g., Madan, Fujiwara, Gerson, & Caplan, 2012;Shenhav & Buckner, 2014 (Shapiro, Siller, & Kacelnik, 2008). This prediction is also convergent with the notion that a fundamental purpose of movements is to obtain rewards, leading people to move faster when a higher value reward is the predicted goal (e.g., Haith, Reppert, & Shadmehr, 2012;Madan, 2013).…”
Section: Introductionsupporting
confidence: 89%
“…This secondary result provides additional correlational evidence for a relationship between the time allotted to a decision and the risk preference exhibited for the decision. Other studies have also found that participants respond faster to higher value decisions (e.g., Shenhav & Buckner, 2014;Tobler et al, 2006). This connection between reward value and RT could also be thought of as a potentiation of motivated movements (Madan, 2013).…”
Section: Discussionmentioning
confidence: 80%
“…The prefrontal cortex has consistently been found to be involved in decision-making and emotion regulation in different experimental paradigms and modalities (Mitchell, 2011;Shenhav and Buckner, 2014). The dorsomedial PFC is believed to be involved in the encoding of rewardrelated information, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…13 Third, extensive disclosure can be associated with lower satisfaction 14 and increased anxiety. 15 This analysis suggests that the best way to respect individual subjects is not to disclose to all potential subjects the information that any single potential subject might consider important. Rather, investigators should explain that enrollment involves helping to assess the treatments under study, disclose any added risks, disclose any information that is important for most subjects, and then discuss with the individual any questions or concerns that they may have.…”
Section: The Costs Of Extensive Disclosurementioning
confidence: 99%